The clinical significance of serum adipocytokines level in patients with lung cancer - Li, Fanfan; Cao, Yanan; Li, Jingjing; Gao, Cong; Dong, Xiang; Ren, Pengfei; Meng, Chenxu; Chen, Chanjuan (Journal of Thoracic Disease, 2019)
Background: Adipocytokines were known to play a relevant role in metabolism, inflammation responses and carcinogenesis of several malignancies. Our aims were to detect the expression of serum adipocytokines, explore their potential diagnostic ability and relationship with clinicopathological characteristics of lung cancer. Methods: Adipocytokines, insulin-like growth factor binding protein 1 (IGFBP-1), resistin, tumor necrosis factors (TNFα), TNF RI and TNF RII, vascular endothelial growth factor (VEGF), leptin, interleukin (IL)-6 and IL-10, chemerin, brain-derived neurotrophic factor (BDNF), plasminogen activator inhibitor-1 (PAI-1) were assessed in 49 untreated lung cancer patients and 20 healthy controls. The protein chip was used to detect the serum levels of adipocytokines. Results: Lung cancer patients exhibited significantly elevated serum IGFBP-1, TNF RI, VEGF, TNF RII, PAI-1 and IL-6 levels compared to controls (P